The difficulties facing the teachers and teachers of the Rusafa/2 preparatory to practice Sports activities - Dawood, Heba (Al-Adab Journal, 2024)
The study aimed to identify the difficulties that the teachers of the teachers of the Rusafa/2 preparators from the exercise of sports activities were formed, and the research sample consisted of (30) a teacher and a school out of the total community of origin (60) of the teachers and teachers of the Rusafa/2 Education – numbers that were chosen in a random manner from the study community. The researcher used the descriptive approach to its current study, and the study included on Four areas of the field of sporting capabilities, the health and physical field and the third field are difficulties related to the social aspect and the field of scientific activity, and the study found that there is no relationship between the difficulties of practicing sports activities with teachers and teachers in the directorate, attributed to the gender variable, while it showed a relationship between the difficulties of practicing sports activities with Teachers and teachers of the preparatory education in the Rusafa/2 directorates attributed to the age variable, as well as the study revealed a relationship between difficulties related to the health and physical field of teachers and teachers in middle schools, attributed to the variable of the scientific qualification, there is also a relationship between the difficulties of practicing sports activities as a whole with teachers and teachers in the preparations.The directorates are attributed to the educational qualification variable. The study recommended the need to provide adequate and appropriate sports tools and devices for the physical education department in the directorate and provide the department with the facilities and facilities for sports activity (gyms, open and open fields and sports fields, rooms to switch clothes) and the need to review the planning and organization of sports activity so that it does not lead to conflict with times And the conditions of the work of teachers and teachers to practice sports activity and pay attention to security and safety factors. when exercising sports.